The effect of Sanitary and Phytosanitary measures on Vietnam's rice exports - Nguyen Thi Thu Thuong (EconomiA, 2018)
We have witnessed increasing concerns about the impacts of food safety standards on agricultural trade. This paper explores how Sanitary and Phytosanitary (SPS) measures affect Vietnam's rice exports. Using different estimation methods to handle overdispersion and zero trade flows for data of Vietnam's rice exports to 20 major importing countries over the period 2000-2015 based on gravity model, the results show that, although GDP, population, distance and production are still vital factors, the SPS measures imposed by importing countries have significant impacts on Vietnam's rice export. The findings suggest that importers implementing SPS measures have experienced considerably lower trade with Vietnam compared to importers that do not use a phytosanitary treatment. However, this effect decreases when income of importers increases.
Keywords: F13; Q17; Q18; C33; 330; Export; Gravity model; Rice; Sanitary and Phytosanitary measures